PUBLIC-PRIVATE PARTNERSHIP: LEARNING FROM THE DEVELOPMENT OF JOGJA AGRO TECHNO PARK - Rahmat, Al Fauzi; Pribadi, Ulung (POLITICO, 2020)
Public-Private Partnerships (PPP) are often seen as an ideal scheme for infrastructure provision when the government is hampered by human and financial resources. Therefore, the government can involve the private sector in playing a role in the successful implementation of infrastructure. This article aims to identify the factors affecting readiness using a public-private partnership (PPP) in the development of Jogja Agro Techno Park (JATP) as a priority development acceleration program in Special Region of Yogyakarta Province. Furthermore, this research uses a descriptive method with qualitative approach. Therefore, the data findings thought in-depth interviews and several kinds of literature. The data findings analysis in this research using NVivo 12 plus software, this qualitative tool is able to provide capture coding rates from interview results that display the intensity level. The result of this research indicated that the dominant variable comes the Local Government Commitment aspects and Institutional Coordination, in which the resulted coding intensity value of Crosstab Query is 28.57%. It is related to the DIY government that has strong institutional level support and its commitment to sustainability in the development of the JATP priority program. Moreover, the high percentage indicators come from the Coordination with Private Sector and Availability of Special Institution. Besides it, other factors found in several aspects of HR Competence and Financial Capacity are did not become play an important role from DIY’s Government in readiness for a PPP scheme in JATP development. This is because financial human resource competencies and also financial capability have been managed by TPSD as an ad-Hock agency devoted to handling PPP schemes. So that the factors of readiness are not necessary to adjust the institutional structure because it has been able to be coordinated based on their respective duties and functions.